IOT-Based Cultural Movement And Monitoring Systems With Renewable Energy Utilities - Charis Fathul Hadi; Untung Suryadhianto (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
The procedure of watering for and keeping track of the temperature and humidity levels in the room has a significant impact on the growth and productivity of oyster mushroom plants. It is often believed to be less effective and efficient because people in the Banyuwangi district perform the irrigation process conventionally with human aid. In order to construct digital businesses, artificial intelligence, cognitive technology, and (IoT) are being developed. People's daily lives are becoming more advanced and connected because to this transformation. This will encourage the creation of fresh innovations. Given this context, the idea to undertake research on the method of automatically and continuously monitoring watering (spraying) mushroom production using the Internet of Things (IoT) developed. In order to improve the effectiveness and productivity of mushroom cultivation, this instrument is designed with a temperature sensor (LM35) to monitor the humidity conditions of oyster mushroom plants. It is also fitted with a solar renewable energy system. In order to improve the effectiveness and productivity of mushroom cultivation, this instrument is designed with a temperature sensor (LM35) to monitor the humidity conditions of oyster mushroom plants. It is also fitted with a solar renewable energy system. The five steps of this study's execution were: a needs analysis; tool design; tool prototype; prototype testing; and conclusion. According to test results, the IoT-based control system for watering mushroom cultivation has an average error of 0.1% when measuring temperature and an average error of 2.66% when measuring humidity. This is almost perfect in terms of sensor readings, indicating that it can be used properly. While the success rate for the spray control system using the IoT system after five trials was 100%, the voltage, current, and power for solar panels were 17.60 V, 4.10 A, and 55.7 Watt at 14.00 during the day.